Аналіз використання графових структур з циклами при розробці інформаційних систем - Бітков, О. О. (ХНУРЕ, 2023)
The issues of using graphs that have cycles to solve problems in information systems are considered. Applied problems that are solved in the process of developing information systems require the improvement of graph models and the adaptation of methods and approaches to the specifics of their application and research. Varieties of graph models with cycles are studied: Euler and Hamiltonian graphs